Soft Skills Training for English Classes to Develop Students’ Quality - Nurlaila, Nurlaila; Fadhillah, Nurul (Journal of English Education and Teaching, 2023)
Some training programs had been conducted to improve students’ soft skills during their study at the State of Islamic Institute (IAIN) of Lhokseumawe, but there was still a lack of consensus on the most effective approaches. This study aimed at increasing students' and graduates’ quality using specific approaches including soft skills training. The population of the research was all English lecturers and All the Students in the first semester who took English Subject at IAIN Lhokseumawe. The sample of this research was four English lecturers and 80 students from four Faculties of IAIN Lhokseumawe. Research and Development (R&D) was conducted to fulfil the needs of the research problems found in the preliminary study. Two kinds of products were developed by researchers namely hardware and software products, prepared, provided and applied by the lecturers. The data was collected using Focus Group Discussions and questionnaires. The data were analyzed quantitatively using SPSS. The result of the tryout of the product developed showed that conducting soft skill training can increase the students’ soft skills at IAIN Lhokseumawe. It was proved that the value of t-count = 24.623 > t-table = 1.66412. It can be understood that soft skills training can bring a significant effect to change university students’ soft skills. It can be applied continuously in English and other classes utilizing products developed to show the sustainability of the university program for getting better quality.